Nurse-led sedation for transfemoral transcatheter aortic valve implantation seems safe for a selected patient population. (30th March 2022) - Kočka, Viktor; Nováčková, Markéta; Kratochvílová, Lenka; Širáková, Andrea; Sulženko, Jakub; Buděšínský, Tomáš; Bystroń, Marian; Neuberg, Marek; Mašek, Petr; Bednář, František; Stern, Michael; Toušek,; et al.
Abstract: Transcatheter aortic valve implantation (TAVI) has become a high-volume procedure with increasing demands on hospital resources. Local anaesthesia with sedation supervised by an anaesthesiology team is the current standard of care. We aimed to describe our experience with a simplified, nurse-led sedation (NLS) protocol. This study enrolled 128 consecutive patients who underwent transfemoral TAVI with self-expandable Evolut R prosthesis between November 2019 and April 2021. Operators selected 50% of patients for NLS based on the clinical expectation of lower risk of procedural difficulties. Nurse-led sedation protocol demanded only mild to moderate levels of sedation. The clinical outcomes were determined from the local TAVI registry and the national mortality database. Baseline patient characteristics were similar in the NLS ( n = 64) and anaesthesiologist-led sedation (ALS) ( n = 64) groups except higher prevalence of diabetes mellitus (48.4% vs. 31.3%, P = 0.035) and peripheral vascular disease (20.3% vs. 7.8%, P = 0.036) in the ALS group. There was a trend for the larger prostheses used in the ALS group ( P = 0.058). The procedural results did not differ, and coronary care team backup was rarely needed in the NLS group (6% of patients). The in-hospital outcomes were identical from both clinical and echocardiography perspectives, and 30-day mortality was low in both groups (1.5%). For the NLS group, preparation in the catheterization laboratory was quicker by 6.4 min ( P = 0.01), and intensive care unit stay was shorter (2.03 vs. 3.48 days, P = 0.001). In conclusion, the NLS for the selected transfemoral TAVI population seems safe.